ГІгієнічна оцінка шуму: проблема адекватності - Колганов, А.В.; Мищенко, І.А. (Актуальні проблеми транспортної медицини, 2013)
З метою підвищення адекватності гігієнічної оцінки проведено дослідження, результати якого показують можливість доповнення загальновизнаної енергетичної моделі для непостійного шуму оцінкою його інформаційних характеристик. Гіпотеза обгрунтовується тим, що, з точки зору теорії аналізаторів, основною для них є функція зв'язку. Проілюстрована методика розрахунку таких характеристик. На прикладі непостійних шумів, характерних для деяких робочих місць у вугільній та металургійній промисловості, із застосуванням дисперсійного та регресійного аналізу показано, що в зміну порогів слухової чутливості достовірний внесок вносять інформаційні характеристики непостійного шуму (ентропія, кількість перероблюваної інформації). Зроблено висновок про їх зв'язок з технологічним процесом, що дозволяє робітнику використовувати непостійний шум, як неінструментальне джерело інформації та необхідності подальшого вивчення подібних біологічних ефектів в інших галузях промисловості та на транспорті. С целью повышения адекватности гигиенической оценки, проведено исследование, результаты которого показывают возможность дополнения общепризнанной энергетической модели для непостоянного шума, оценкой его информационных характеристик. Гипотеза обосновывается тем, что, с точки зрения теории анализаторов, основной для них является функция связи. Проиллюстрирована методика расчета таких характеристик. На примере непостоянных шумов, характерных для некоторых рабочих мест в угольной и металлургической промышленности, с применением дисперсионного и регрессионного анализа показано, что в изменение порогов слуховой чувствительности достоверный вклад вносят информационные характеристики непостоянного шума (энтропия, количество перерабатываемой информации). Сделан вывод об их связи с технологическим процессом, что позволяет рабочему использовать непостоянный шум, как неинструментальный источник информации и необходимости дальнейшего изучения подобных биологических эффектов в других отраслях промышленности и на транспорте. The results of investigation shows that well-known energetical model for changeable noise should be complete with assessment of its informational characteristics for improving of hygienic assessment adequacy. Method of calculation of these characteristics is illustrated. The hypothesis is based on main analyzers function is connection according the analyzers theory. Each analyzer, including auricular, supplies the body with sensory information, providing, along with it, their own safety. In the noice conditions the workers are forced to use it as an additional sourse of information. For some occupations (operators of seismic forecast, telephone operators, traffic controllers etc.) detection of acoustic signal in background noise is essence of activity. These analyzers functions have a contradiction: on the one hand, the analyzer should be very sensitive, and on the other hand, it should increase the thresholds of perception for own safety. It is established that informational characteristics of changeable noise (entropy, the amount of processed data) make a credible contribution in the change of the thresholds of auditory sensitivity (for example of changeable noises for some work places in the coal and steel industry with using dispersion and regression analysis). Their significance is determined by strong relationship with technological proses. At the begining of rolled metal has a very high temperature and during processing generates pulses of mid-range 0.9;1.2 s. with a relatively large (up to 0.4 s) the leading front time increasing. In the area of cutting shears metal is cold with high-frequency and short pulses (0.3;0.5 s) with the leading front time increasing to 0.1 seconds. etc. A conclusion about their relationship with technological proses which allows workers to use a changeable noise as non-instrumental sourse of information and nessesaty of further investigation such biological effects in different branches of industry and transport is made.